Cx43 Overexpression in Osteocytes Prevents Osteocyte Apoptosis and Preserves Cortical Bone Quality in Aging Mice. (26th February 2018) - Davis, Hannah M; Aref, Mohammad W; Aguilar‐Perez, Alexandra; Pacheco‐Costa, Rafael; Allen, Kimberly; Valdez, Sinai; Herrera, Carmen; Atkinson, Emily G; Mohammad, Arwa; Lopez, David; Harris, Marie A; Harris, Stephen E; et al.
ABSTRACT: Young, skeletally mature mice lacking Cx43 in osteocytes exhibit increased osteocyte apoptosis and decreased bone strength, resembling the phenotype of old mice. Further, the expression of Cx43 in bone decreases with age, suggesting a contribution of reduced Cx43 levels to the age‐related changes in the skeleton. We report herein that Cx43 overexpression in osteocytes achieved by using the DMP1‐8kb promoter (Cx43 OT mice) attenuates the skeletal cortical but not trabecular bone phenotype of aged, 14‐month‐old mice. The percentage of Cx43‐expressing osteocytes was higher in Cx43 OT mice, whereas the percentage of Cx43‐positive osteoblasts remained similar to wild‐type (WT) littermate control mice. The percentage of apoptotic osteocytes and osteoblasts was increased in aged WT mice compared with skeletally mature, 6‐month‐old WT mice, and the percentage of apoptotic osteocytes, but not osteoblasts, was decreased in age‐matched Cx43 OT mice. Aged WT mice exhibited decreased bone formation and increased bone resorption as quantified by histomorphometric analysis and circulating markers compared with skeletally mature mice. Further, aged WT mice exhibited the expected decrease in bone biomechanical structural and material properties compared with young mice. Cx43 overexpression prevented the increase in osteoclasts and decrease in bone formation on the endocortical surfaces and the changes in circulating markers in the aged mice. Moreover, the ability of bone to resist damage was preserved in aged Cx43 OT mice both at the structural and material level. All together, these findings suggest that increased Cx43 expression in osteocytes ameliorates age‐induced cortical bone changes by preserving osteocyte viability and maintaining bone formation, leading to improved bone strength. © 2018 American Society for Bone and Mineral Research.